2018
DOI: 10.1038/s41598-017-18682-3
|View full text |Cite|
|
Sign up to set email alerts
|

Zika Virus in Salivary Glands of Five Different Species of Wild-Caught Mosquitoes from Mexico

Abstract: Zika virus (ZIKV) is a mosquito-borne pathogen, and Aedes aegypti has been identified as the main vector of the disease. Other mosquito species in the Aedes and Culex genera have been suggested to have the potential for being competent vectors based on experimental exposition of mosquitoes to an infectious blood meal containing ZIKV. Here, we report the isolation in cell culture of ZIKV obtained from different body parts of wild-caught female mosquitoes (Ae. aegypti, Ae. vexans, Cx. quinquefasciatus, Cx. coron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 25 publications
2
53
0
Order By: Relevance
“…However, the role of the southern house mosquito Culex (Culex) quinquefasciatus, typically the most abundant neotropical urban species, has remained controversial. Only two fieldbased studies have found any evidence of natural C. quinquefasciatus infection by ZIKV [6,7]. However, in both reports, the amount of ZIKV as measured by RNA titres using RT-qPCR was unlikely to be associated with transmission-competence; for example, Guedes et al [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of the southern house mosquito Culex (Culex) quinquefasciatus, typically the most abundant neotropical urban species, has remained controversial. Only two fieldbased studies have found any evidence of natural C. quinquefasciatus infection by ZIKV [6,7]. However, in both reports, the amount of ZIKV as measured by RNA titres using RT-qPCR was unlikely to be associated with transmission-competence; for example, Guedes et al [6].…”
mentioning
confidence: 99%
“…However, in both reports, the amount of ZIKV as measured by RNA titres using RT-qPCR was unlikely to be associated with transmission-competence; for example, Guedes et al [6]. reported Ct values in field-collected pools of C. quinquefasciatus pools >37, while the salivary gland pools analysed Elizondo-Quiroga et al were cell culture-passaged prior to RNA assay [7], eliminating the ability to directly assess transmission potential.…”
mentioning
confidence: 99%
“…Recently, Zika virus was detected in the salivary glands in female Culex mosquitoes, coronator, Culex tarsalis, and Aedes vexans captured in wild Mexican forests, suggesting that all mosquito species could easily transmit arboviruses to bats and humans and that strains could be amplified naturally in Chiroptera and other vertebrates (Elizondo-Quiroga et al, 2018). While the urban cycle of DENV is maintained between humans and A. aegypti, the mechanisms for maintaining DENV in the jungle cycle are still unknown, despite the fact that DENV has been detected by molecular methods in wildlife in different countries.…”
Section: Vectorsmentioning
confidence: 99%
“…tarsalis, and Cx. quinquefasciatus have been reported as potential vectors for the transmission of the Zika virus in Brazil, China, and Mexico (Guo et al 2016;Guedes et al 2017;Elizondo-Quiroga et al 2018).…”
Section: Introductionmentioning
confidence: 99%